2020
DOI: 10.1152/ajpgi.00216.2019
|View full text |Cite
|
Sign up to set email alerts
|

TGR5 signaling mitigates parenteral nutrition-associated liver disease

Abstract: Bile acid receptors regulate the metabolic and immune functions of circulating enterohepatic bile acids. This process is disrupted by administration of parenteral nutrition (PN), which may induce progressive hepatic injury for unclear reasons, especially in the newborn, leading to PN-associated liver disease. To explore the role of bile acid signaling on neonatal hepatic function, we initially observed that Takeda G protein receptor 5 (TGR5)-specific bile acids were negatively correlated with worsening clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Our understanding role of BAs has evolved from simple detergents to hormones intimately related to multiple metabolic processes, revealing important roles of BAs in dyslipidemia and type 2 diabetes 36 . BAs are a significant source of host–microbiome interaction via cellular receptors such as TGR5 ( Gpbar1 ) 37 and FXR ( Nrlh4 ) 36 . Therefore, BA composition is interrelated with metabolic hormones such as leptin 38 , 39 , resistin 40 , ghrelin, GLP-1 (glucose-like peptide-1), and peptide YY 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding role of BAs has evolved from simple detergents to hormones intimately related to multiple metabolic processes, revealing important roles of BAs in dyslipidemia and type 2 diabetes 36 . BAs are a significant source of host–microbiome interaction via cellular receptors such as TGR5 ( Gpbar1 ) 37 and FXR ( Nrlh4 ) 36 . Therefore, BA composition is interrelated with metabolic hormones such as leptin 38 , 39 , resistin 40 , ghrelin, GLP-1 (glucose-like peptide-1), and peptide YY 41 .…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the recent Letter to the Editor of Am J Physiol Gastrointestinal Liver Physiol by Dr. Saumya Pandey, which emphasized the need for deeper understanding of the underpinning mechanisms of parenteral nutrition (PN)-associated liver disease (PNALD) and Takeda-G protein receptor-5 (TGR5) signaling. This letter highlighted our recently published work that employed human and murine samples provided PN alimentation to define the role of TGR5 signaling upon hepatic stress and homeostasis (1). The letter also highlighted the insightful findings of Zhan et al 2, which identified additional changes in hepatic retinoid acid-related orphan receptor-␣ (ROR␣), hepatic nuclear and transmembrane receptors, and sterol-exporters as potential influencers of PNALD development.…”
Section: Replymentioning
confidence: 76%
“…Our understanding role of BAs has evolved from simple detergents, to hormones intimately related to multiple metabolic processes, revealing important roles of BAs in dyslipidemia and type 2 diabetes. 40 BAs are a significant source of host-microbiome interaction via cellular receptors such as TGR5 41 and FXR. 40 Therefore, BA composition is interrelated with metabolic hormones such as leptin, 42,43 resistin, 44 ghrelin, GLP-1 (glucose-like peptide-1) and peptide YY.…”
Section: Discussionmentioning
confidence: 99%